2021
DOI: 10.1371/journal.pbio.3001097
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense-mediated decay controls the reactivation of the oncogenic herpesviruses EBV and KSHV

Abstract: The oncogenic human herpesviruses Epstein–Barr virus (EBV) and Kaposi’s sarcoma-associated herpesvirus (KSHV) are the causative agents of multiple malignancies. A hallmark of herpesviruses is their biphasic life cycle consisting of latent and lytic infection. In this study, we identified that cellular nonsense-mediated decay (NMD), an evolutionarily conserved RNA degradation pathway, critically regulates the latent-to-lytic switch of EBV and KSHV infection. The NMD machinery suppresses EBV and KSHV Rta transac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Gammaherpesviruses have evolved multiple mechanisms to repress expression of their ORF50 homologs, achieving exquisite control of entry into the lytic cycle. Recent work has shown that ORF50 transcripts, by including splice junctions downstream of the ORF50 stop codon are degraded by nonsense mediated decay that must be subverted to achieve lytic cycle entry [ 45 , 46 ]. In the case of EBV, further repression is achieved by extensive methylation of the Rta promoter in B lymphocytes, the site of latency, that requires binding of Zta to methylated response elements to overcome [ 10 , 11 , 13 , 15 , 16 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gammaherpesviruses have evolved multiple mechanisms to repress expression of their ORF50 homologs, achieving exquisite control of entry into the lytic cycle. Recent work has shown that ORF50 transcripts, by including splice junctions downstream of the ORF50 stop codon are degraded by nonsense mediated decay that must be subverted to achieve lytic cycle entry [ 45 , 46 ]. In the case of EBV, further repression is achieved by extensive methylation of the Rta promoter in B lymphocytes, the site of latency, that requires binding of Zta to methylated response elements to overcome [ 10 , 11 , 13 , 15 , 16 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since our ChIP assays suggested that Rta/Zta synergy was not operating at the level of promoter binding, we considered the possibility that Zta was increasing the stability of Rta induced transcripts. Indeed, recent reports have shown that modulation of mRNA stability is a key mechanism by which gammaherpesvirus regulate the transition from latent infection to lytic replication [45][46][47]. Hypothesizing that Zta might interfere with the nonsense mediated decay (NMD) pathway to stabilize lytic transcripts, we tested whether NMD inhibition could substitute for Zta expression in increasing the levels of Rta synergy transcripts.…”
Section: Zta Does Not Affect Rna Stability Of the Early Lytic Rta Syn...mentioning
confidence: 99%
“…Emerging studies suggested that mRNA decay pathways play an important role in restricting gamma-herpesvirus reactivation. Proteins involved in nonsense-mediated mRNA decay have been shown by the Gack and Karijolich labs to restrict EBV and KSHV replication ( 54 , 55 ). Our current discovery of multiple proteins within the m 6 A RNA modification pathway as EBV restriction factors further enhances our understanding of the control of herpesvirus reactivation at the RNA level.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, p38 kinase was also recently reported to inhibit nonsense mediated decay (NMD) of RNA in cells with DNA damage [ 107 ]. Since NMD was recently shown to promote degradation of the transcript encoding the BZLF1 and BRLF1 genes in latently infected cells [ 108 ], decreasing NMD of this transcript in the context of the intact viral genome could be another post-transcriptional mechanism by which p38 kinase promotes lytic EBV reactivation.…”
Section: Discussionmentioning
confidence: 99%